Rihanna the seahorse fairy - Meadows, Daisy (Meadows, Daisy. Magical animal fairies, 2012)
Rachel and Kirsty are going to an outdoor adventure camp, but Jack Frost has stolen the seven magical animals from their fairies and they must rush to help Rihanna the Seahorse Fairy save her seahorse, Bubbles, that is somewhere in the camp's lake.